2015
DOI: 10.1111/afe.12110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of logging and coarse woody debris harvest on lepidopteran communities in the eastern deciduous forest of North America

Abstract: 1 Expansion of biomass energy production using woody feedstocks is being accomplished through post-timber harvest removal of coarse woody debris > 10 cm. The effect of this management on forest Lepidoptera is poorly known. 2 The present study aimed to determine whether forest lepidopteran diversity and species composition were affected by two silvicultural disturbances: timber harvest and post-logging removal of coarse woody debris > 10.0 cm in diameter. 3 In 2014, Lepidoptera were sampled from nine forest sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The Macroheterocera, a group commonly called 'macromoths' that includes the moth superfamilies Bombycoidea, Drepanoidea, Geometroidea, Lasiocampoidea, and Noctuoidea (Kawahara et al, 2019) has proven useful in assessing the impacts of logging in various forest ecosystems, including tropical and subtropical forests (Willot, 1999;Kitching et al, 2000;Hilt et al, 2006;Hawes et al, 2009;de Camargo et al, 2016), temperate deciduous forests of North America (Summerville & Crist, 2002;Summerville et al, 2004;Parrish & Summerville, 2015;Summerville & Marquis, 2017), and temperate coniferous forests of Japan (Moon et al, 2018) and eastern North America (Thomas, 2002). Macromoths are well suited for such studies because they are abundant, diverse, easily sampled, and taxonomically well-known (Miller & Hammond, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Macroheterocera, a group commonly called 'macromoths' that includes the moth superfamilies Bombycoidea, Drepanoidea, Geometroidea, Lasiocampoidea, and Noctuoidea (Kawahara et al, 2019) has proven useful in assessing the impacts of logging in various forest ecosystems, including tropical and subtropical forests (Willot, 1999;Kitching et al, 2000;Hilt et al, 2006;Hawes et al, 2009;de Camargo et al, 2016), temperate deciduous forests of North America (Summerville & Crist, 2002;Summerville et al, 2004;Parrish & Summerville, 2015;Summerville & Marquis, 2017), and temperate coniferous forests of Japan (Moon et al, 2018) and eastern North America (Thomas, 2002). Macromoths are well suited for such studies because they are abundant, diverse, easily sampled, and taxonomically well-known (Miller & Hammond, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although a recent suite of studies (Summerville & Crist, 2008;Summerville, 2011;Highland et al, 2013;Parrish & Summerville, 2015;Summerville & Marquis, 2017) has shown that the community composition of North American macromoths responds to a variety of factors including habitat disturbance, the degree to which macromoth communities differ between natural and managed forests is unknown for most North American forest ecosystems. In particular, no studies have assessed the impacts of logging on macromoth communities in coniferous forests of the Pacific Northwest, where there are over 1500 macromoth species (Miller & Hammond, 2000;Pohl et al, 2015).…”
Section: Introductionmentioning
confidence: 99%